Weaponising the Internet of Things. Issue 10 (October 2017) - Mansfield-Devine, Steve
Abstract : It seems that as fast as we develop defences for our networks and computing devices we also introduce new products with new flaws that criminals and others can exploit. The Internet of Things (IoT) is a case in point. In the rush to connect everything from dolls to CCTV systems to the Internet, security seems to get overlooked, making us all vulnerable. In this interview with penetration tester Ken Munro, a partner at Pen Test Partners, we discover how the most seemingly innocuous product can be turned into a cyber weapon.